Characterization of the Gene Expression Profile of Human Hippocampus in Mesial Temporal Lobe Epilepsy with Hippocampal Sclerosis. (23rd January 2011) - Lachos, Julio; Zattoni, Michela; Wieser, Heinz-Gregor; Fritschy, Jean-Marc; Langmann, Thomas; Schmitz, Gerd; Errede, Mariella; Virgintino, Daniela; Yonekawa, Yasuhiro; Frei, Karl
Abstract : One of the main putative causes of therapy refractory epilepsy in mesial temporal lobe epilepsy (MTLE) with hippocampal sclerosis is the overexpression of multidrug transporters (MDTs) at the blood-brain barrier (BBB). It steps up the removal of antiepileptic drugs (AEDs) out of the brain cells across the BBB resulting in a low concentration of AEDs within the target cells. Some of the mechanisms of AED resistance are most likely to be genetically determined. To obtain more information about the underlying pathophysiology of intractability in epilepsy, we compared the global gene expression profile of human hippocampus and hippocampal-derived microvascular endothelial cells from MTLE with HS patients and controls. At the level of MDT, a significant up-regulation was found for ABCB1 (P-gp), ABCB2, ABCB3, and ABCB4, which was mainly related to endothelial cells. The data on the MDT were validated and extended by quantitative RT-PCR. Surprisingly, inflammatory factors such as interleukins (IL-1 α, IL-1 β, IL-6, and IL-18) and cytokines (TNF- α and TGF- β 1) were found to be up-regulated in hippocampal parenchyma. The overexpression of P-gp, IL-1 β, and IL-6 was also confirmed by immunohistochemistry (IHC). Our results suggest that complex expression changes of ABC-transporters may play a decisive role in pharmacoresistance in MTLE. Further studies on the new and unexpected overexpression of inflammatory cytokines may unlock hitherto undiscovered pathways of the underlying pathophysiology of human MTLE.